Biomineralization in loliginid squid statocysts and the use of statoliths to estimate age - Durholtz, Marius Deon (African Centre for Cities, 2026)
The use ofstatoliths to estimate the age ofloliginid squid is critically assessed. Alternating "light" and "dark" layers visible in statoliths viewed with a light microscope are proposed to reflect a daily cycle in statolith mineralization. A "light" and adjacent "dark" layer, known as an increment, are hypothesized to be deposited over a 24 hour period, and hence can be used to estimate the age of squid. Research was directed to the methodological aspects ofthe application ofthe statolith age estimation technique, as well as the physiological processes of statolith mineralization. A method ofpreparing statoliths of chokka squid Loligo vulgaris reynaudii for increment counting using light microscopy (LM) is described. The performance ofthe method is assessed by comparing the results with those obtained using scanning electron microscopy (SEM). The LM method is superior to the SEM method in that fewer specimens which require interpolation or extrapolation of increment numbers is obtained. For any given reader, the null hypothesis that increment counts obtained using LM were similar to those obtained using SEM could not be rejected. Either method can be used to count increments in chokka statoliths with similar effectiveness. Between-reader differences in increment interpretation and counting were apparent in the LM results, but not in SEM. The problem of interpretation ofstatolith microstructure may introduce a significant source oferror when using LM rather than SEM. The hypothesis that increments in squid statoliths are deposited with a daily frequency was tested for the first time in wild populations, using statolith marking experiments. The results are consistent with daily increment production in adult males of Loligo vulgaris reynaudii. The same result was obtained for the single adult female included in the study. Analysis of the errors involved in increment counting highlighted the importance of proper statolith preparation. The error in counting increments in a poorly prepared statolith may be three times higher than that in a well-prepared statolith. The results ofstatolith marking experiments conducted on Lo/igo vulgaris reynaudii in the laboratory were consistent with daily increment production in males, but not in females. Increment deposition rates in males were similar in both field and laboratory conditions, indicating that the results of laboratory experiments of this nature can be justifiably extrapolated to wild individuals. The hypothesis that temperature influences statolith growth and resultant microstructure was tested in a laboratory study ofthe loliginid squid Lolliguncula brevis. Groups ofsquid were subjected to various temperature regimes for extended periods, and the regions of the statolith deposited during the experiments were subsequently examined using laser scanning microscopy. Checks deposited in response to stressful events such as capture and handling are shown to consist ofa series ofprominent increments, rather than reflecting a period ofinterrupted statolith growth. Constant temperature conditions appeared to reduce increment contrast and clarity, presumably due to a dampening of the metabolic cycles associated with increment formation. Average statolith growth rates observed over the course of the experiment showed a strong positive relationship to ambient temperature. A significant sex effect was also apparent, with statoliths of female squid generally growing faster than those of males. Statolith Abstract Page 6 ABSTRACT The use ofstatoliths to estimate the age ofloliginid squid is critically assessed. Alternating "l ight" and "dark" layers visible in statoliths viewed with a light microscope are proposed to renect a daily cycle in statolith mineralization. A "light" and adjacen t "dark" layer, known as an increment, ate hypothesized to be deposited over a 24 hour period, and hence can be used to estimate ihe age of squid. Research was directed to the methodologica l aspects of tile application of the statolith age estimation technique, as well as the physiological processes of statolith minera lization. A method of preparing statoliths ofchokka squid Loligo vulgaris reynaudiifor increment counting using light microscopy (LM) is described. The perfonnance of the method is assessed by comparing the results with those obtained using scanning electro